Implementasi Batas Usia Minimal Perkawinan Berdasarkan Undang-Undang No. 16 Tahun. 2019 dan Hukum Adat di Dusun Adat Kasepuhan Citorek Barat Kecamatan Cibeber Kabupaten Lebak - Adhiyani Lu’Luul Karimah; Ahmad Zaini; Iin Ratna Sumirat (CV. Ulil Albab Corp, 2022)
Underage marriage becomes a polemic and dilemma when faced with customary law. Juridically this marriage is indeed prohibited but in fact it is still ongoing and continues to increase in certain indigenous peoples. This study aims to determine the level of presentation of underage marriages in the traditional hamlet of Kasepuhan Citorek Barat, Citorek Barat Village, Cibeber District, Lebak Regency. Factors causing the occurrence and impact of the Underage Marriage. This research is a qualitative research with a case study or field study approach. Data collection is done by observation, interviews and documentation. The data were analyzed by descriptive analysis technique. The results of the study stated that underage marriages in the Kasepuhan Indigenous Hamlet, Citorek Village, Cibeber Lebak District are increasing from year to year, this shows that the Marriage Law no. 16 of 2019 as an amendment to Law no. 1 of 1974 has not run effectively. The causal factors are economic factors, education, parents and prevailing customs. Meanwhile, the impacts include negative impacts, namely; Can cause severe depression, Can cause divorce due to immature age, Barriers to education, Can cause domestic violence, Economic difficulties can make children neglected, Underage workers appear, Risk of dying at a young age and Increased infant mortality. Meanwhile, the positive impacts of underage marriage include; Reducing the burden on parents and preventing the occurrence of disobedience and promiscuity.